Principal component and hierarchical cluster analysis to select natural elicitors for enhancing phytochemical content and antioxidant activity of lettuce sprouts - Viacava, Gabriela Elena (2015)
Sprouts have received increasing attention in recent years because of their potential dietary value. Additionally, the efficient production of sprouts with high levels of phytochemicals and antioxidants is desirable. However, no studies were performed on lettuce sprouts. The phytochemical content and antioxidant activity of lettuce sprouts were studied. Moreover, natural elicitors (chitosan and tea tree) were applied as soaking solution during different times or as exogenous daily spraying during germination in order to enhance the phytochemical content of the sprouts. Data was analyzed using multivariate analysis. Untreated lettuce sprouts presented a significant higher content of total phenolics and flavonoids, and antioxidant activity (through DPPH and TEAC assays) than those reported for mature heads of different green lettuce cultivars. Germination percentage was negatively affected by high elicitors concentrations and long contact times. Based on multivariate analysis, only sprouts daily sprayed with elicitors (tea tree 0.18, 0.27, 0.36% v/v and chitosan 0.25, 0.5, 1.0% w/v) presented a significant higher content of phytochemicals and antioxidant activity than the others. Therefore, exogenous application of chitosan and tea tree can stimulate the biosynthesis of phytochemicals, improving the nutritional value of lettuce sprouts.